Pemikiran imam Syafi'i tentang hubungan antara akhlak dengan menuntut ilmu dalam pendidikan Islam modren - Dinda Nabilah; Dina Mariana Hasibuan; M. Yunus Siregar; Sehat Sultoni Dalimunthe (Jurnal Pendidikan Agama Islam, 2026)
This study aims to examine the concept of students’ learning ethics toward teachers in the classical Islamic education tradition through the thoughts of Imam al-Shafi’i. This research employs a qualitative approach using the library research method by reviewing classical works and contemporary academic literature. The findings reveal that in classical Islamic education, the relationship between student and teacher is not merely intellectual but also spiritual and moral. The ethics of students toward teachers include respect, sincerity, perseverance in seeking knowledge, and the consistent practice of learned knowledge. Meanwhile, teachers’ morality reflects exemplary conduct, honesty, patience, and compassion in guiding students. These values remain highly relevant to modern education systems facing crises of character and moral degradation. Therefore, this study contributes to strengthening the paradigm of Islamic education based on morality and spirituality. It recommends integrating classical educational values into Islamic education curricula to cultivate knowledgeable individuals with strong moral character and integrity.